PERANCANGAN SISTEM PAKAR KESEHATAN ANAK BERBASIS HANDPHONE MENGGUNAKAN JAVA 2 MICRO EDITION - Rosyadi, Imron; Kamaluddin, Ridlwan (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2009)
At majority of developing countries such as Indonesia , Acces society to health medium still very limited. In Indonesia , only there are 0,13 doctor for 1.000 soul, 0,62 nurse for 1.000 soulmand 0,2 midwife for 1.000 soul. In health world, Expert System have a lot of used in assisting diagnosis of some disease. Along with technological growth , health world have also eploited handheld computer (such as PDA, smart phone and also ordinary handphone) to assist helath handling. Technological appearance of java 2 Micro Edition from sun Microsystems, progressively facilitate handheld computer use in PDA and also Handphone to assist various productive application and also amusement. This research purpose for design, implemented and performance test  of handphone expert system of health based with java 2 Micro Edition. This research consisted of three phase. The first phase was scheme of expert system phase. Second phase was implementation of handphone expert system with J2ME program. The third phase was examination of expert system. The examination of expert system software was conducted through alpha test and beta test. Alpha test alpha conducted by system designer while beta test conducted by consumer system. Handphone-based expert system for child health diagnose has been developed using java 2 Micro Edition technology. The system has been implemented in Siemens handphone type C65. The system has been tested with good and reliable results. Expert system based on designed by J2ME technology has been developed and implemented with Siemens handphone type C65 hardware.